Oil and gas treatment international company in Colombia (2012)
The only objective of this thesis was to find out if it was or not a good idea and investment to launch Prosernat in Colombia, in other words, if it would be profitable to open Porsernat’s offices in Colombia and start operating in the country in a direct way. Today is very easy for any newspaper reader to say that the industry of Oil & Gas is in a very good shape and growing very fast, however, what this people probably do not know is the potential that countries like Colombia have in this subject, and even further,, the political, economical and social strengths and facilities to actually invest in this countries.